Problem 1
Answer: C) 132.6
--------------------
Step-by-step explanation:
a1 = 1.7 = amount of concrete for the first step
a4 = x = amount of concrete for the fourth step
Sn = sum of the first n terms of an arithmetic sequence
Sn = (n/2)*(a1 + an)
S4 = (4/2)*(a1 + a4)
S4 = 2(1.7+x)
S4 = 2x+3.4
S4 = 17
2x+3.4 = 17
2x = 17-3.4
2x = 13.6
x = (13.6)/2
x = 6.8
We need 6.8 cubic feet of concrete for the fourth step. We'll use this value to help us find the common difference d
an = nth term of an arithmetic sequence
an = a1 + d(n-1)
a4 = a1 + d(4-1)
a4 = a1 + 3d
6.8 = 1.7 + 3d
6.8-1.7 = 3d
5.1 = 3d
(5.1)/3 = d
1.7 = d
d = 1.7
Coincidentally, the common difference is the same as the first term. This won't always happen.
Now we can compute the 12th term
an = a1 + d(n-1)
a12 = 1.7 + 1.7(12-1)
a12 = 20.4
which is then used to find the sum of the first 12 terms
Sn = (n/2)*(a1 + an)
S12 = (12/2)*(a1 + a12)
S12 = 6(1.7 + 20.4)
S12 = 132.6
=============================================================
Problem 2
Answer: C)
![x^2 + (y-10)^2 = 225\\\\](https://img.qammunity.org/2022/formulas/mathematics/college/awveapjb5tc1f17kidgsvxmho8ygtxpw04.png)
--------------------
Step-by-step explanation:
The center is (h,k) = (0,10) which is where the nozzle is located.
The distance from (0,10) to (0,25) is 15 units, so r = 15.
Also, the distance from (0,10) to (0,-5) is also 15 units.
Plug those values into the equation below.
![(x-h)^2 + (y-k)^2 = r^2\\\\(x-0)^2 + (y-10)^2 = 15^2\\\\x^2 + (y-10)^2 = 225\\\\](https://img.qammunity.org/2022/formulas/mathematics/college/43u5a9697lfe3ncgwzmmwqxv91s7t42246.png)
That equation represents the boundary of the circle, which is where the water can reach.
=============================================================
Problem 3
Answer: B) 2.336 ft
--------------------
Step-by-step explanation:
- a1 = height 1st bounce = 6.7 ft
- a2 = height 2nd bounce = 81% of a1 = 81% of 6.7 = 0.81*6.7 = 5.427
- a3 = height 3rd bounce = 81% of a2 = 81% of 5.427 = 0.81*5.427 = 4.39587
Or note that,
a3 = 0.81*(a2) = 0.81*(0.81a1) = a1*(0.81)^2 = 6.7*(0.81)^2 = 4.39587
which must mean,
- a4 = a1*(0.81)^3
- a5 = a1*(0.81)^4
- a6 = a1*(0.81)^5
This is based off the idea that
![a_n = a(r)^(n-1)](https://img.qammunity.org/2022/formulas/mathematics/college/dwauw5x4pdir1hu429wb0s5aa90m01ji09.png)
So,
a6 = a1*(0.81)^5
a6 = 6.7*(0.81)^5
a6 = 2.33614554867
a6 = 2.336